Distributed leader-following consensus of nonlinear multi-agent systems with nonlinear input dynamics - Shi, Y.; Yin, YanYan; Wang, Song; Liu, Y.; Liu, F. (Elsevier BV, 2018)
© 2018 Elsevier B.V. This paper addresses the problem of distributed leader-following consensus for a multi-agent system with an affine nonlinear term. The communication topology we adopt is an undirected connected graph and the leader sends its information to one or more followers. To make each follower asymptotically synchronize with the leader, a nonlinear distributed control protocol is proposed. Using a Lyapunov function and a matrix theory, we establish sufficient conditions which ensure the consensus of these nonlinear multi-agent systems. Finally, a numerical simulation is provided to verify the effectiveness and usefulness of the developed method.